A longitudinal case study of step characteristics in a world class sprint athlete - Bezodis, I. N.; Salo, A. I. T.; Kerwin, D. G. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The relative importance of step length (SL) and step frequency (SF) to maximum velocity sprinting is not yet fully understood. One elite male sprinter was studied during five months of training. Step velocity, SL and SF were calculated from 50 Hz video, using manual digitization and 2D DLT, for a total of 113 steps taken from the maximum velocity phase of training sprints. Mean values were calculated for each session and tracked against training diary information gathered from the athlete's coach. Chronological information showed that as the athlete's training progressed, a link between velocity and SF was maintained whilst mean session SL remained relatively unchanged throughout. For the athlete studied, changes in step velocity as a result of training were shown to occur as a consequence of changes mainly in SF.